2012
DOI: 10.1371/journal.pone.0042204
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of the Effect of Fluoride on the Acquired Enamel Pellicle

Abstract: The acquired enamel pellicle (AEP) is a thin film formed by the selective adsorption of salivary proteins onto the enamel surface of teeth. The AEP forms a critical interface between the mineral phase of teeth (hydroxyapatite) and the oral microbial biofilm. This biofilm is the key feature responsible for the development of dental caries. Fluoride on enamel surface is well known to reduce caries by reducing the solubility of enamel to acid. Information on the effects of fluoride on AEP formation is limited. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 46 publications
1
69
0
11
Order By: Relevance
“…However, the enamel surface modifications showed an effect in the quantity of some proteins, such as histatin-1, a recognized pellicle precursor that was found to be present in low abundance in enamel pellicle from slabs pretreated with APF. In a recent study, the same protein showed lower affinity for HA slabs pretreated with neutral fluoride solution than for HA with no treatment [Siqueira et al, 2012a].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the enamel surface modifications showed an effect in the quantity of some proteins, such as histatin-1, a recognized pellicle precursor that was found to be present in low abundance in enamel pellicle from slabs pretreated with APF. In a recent study, the same protein showed lower affinity for HA slabs pretreated with neutral fluoride solution than for HA with no treatment [Siqueira et al, 2012a].…”
Section: Resultsmentioning
confidence: 91%
“…onstrated that HA discs pretreated for 2 h with different concentrations of neutral fluoride solutions modulate the pellicle composition [Siqueira et al, 2012a]. Although all the results are valuable, from a clinical perspective, the effect of APF on pellicle composition is still not known.…”
mentioning
confidence: 99%
“…We employed an in vivo design that had been used before to evaluate proteins in the AEP that are resistant to removal by acids that mimic extrinsic erosion (citric acid) and caries (lactic acid) [Delecrode et al, 2015b]. Thus, the results obtained here are more realistic than those described in studies involving in vitro [Siqueira et al, 2012a;Masson et al, 2013;Custodio et al, 2015] or in situ [Delecrode et al, 2015a;Delius et al, 2017] protocols. Since our study was conducted in vivo, it was not possible to use other methods of collection, such as sonication or treating the samples with strong detergents that are cytotoxic, such as Triton X-100 or SDS, as has been done in in situ studies [Delius et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Supernatant were carefully removed, separated in aliquots of 50 μL and stored at -80°C. The total protein concentration in each sample was assessed by the micro bicinchoninic acid (Micro BCA) assay [49]. Equal amounts of protein (20 μg) from both experimental and control groups were dried by a rotary evaporator, denatured and reduced for 2 hours by the addition of 200 μL of 4 M urea, 10 mM dithiothreitol (DTT), and 50 mM NH 4 HCO 3 , pH 7.8.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide separation and mass spectrometric analyses were carried out as described previously [49]. The MS/MS spectra were analysed against the streptococcal protein database (Swiss Prot and TrEMBL, Swiss Institute of Bioinformatics, Geneva, Switzerland, http://ca.expasy.org/sprot/) using SEQUEST algorithm in Proteome Discoverer 1.3 software (Thermo Scientific, San Jose, CA, USA) [49].…”
Section: Methodsmentioning
confidence: 99%